Intimate partner violence during pregnancy and maternal and child health outcomes: a scoping review of the literature from low-and-middle income countries from 2016 - 2021 - Thao Da Thi Tran; Linda Murray; Thang Van Vo (BMC, 2022)
Abstract Background Intimate partner violence (IPV) during pregnancy is significantly associated with negative outcomes for both mother and child. Current evidence indicates an association between low levels of social support and IPV, however there is less evidence from low-and-middle income countries (LMIC) than high-income countries. Globally, the COVID-19 pandemic has radically altered how women can access social support. Hence since 2020, studies investigating IPV and pregnancy have occurred within the changing social context of the pandemic. Objective This scoping review summarizes the evidence from LMICs about the effects of IPV during pregnancy on maternal and child health. The review includes the impact of the COVID-19 pandemic on social support as mentioned in studies conducted since 2020. Design Library databases were used to identify papers from 2016 to 2021. These studies reported the maternal and child health outcomes of IPV during pregnancy, and described how social support during pregnancy, and the COVID-19 pandemic, were associated with rates of IPV during pregnancy. Observational study designs, qualitative and mixed methods studies were included. Results Twenty - six studies from 13 LMICs were included. Half (n = 13) were cross sectional studies which only collected data at one time-point. IPV during pregnancy was significantly associated with higher odds of postpartum depression, low birth weight, preterm birth and less breastfeeding in the year after birth. Lower levels of social support increased the odds of experiencing IPV during pregnancy, whilst higher levels of social support reduced antenatal anxiety and depression in women experiencing IPV during pregnancy. Of the four studies that investigated IPV during pregnancy throughout the COVID-19 pandemic, only one compared prevalence before and after the pandemic and unexpectedly reported a lower prevalence. Conclusions Further research on the impact of IPV during pregnancy on maternal and child outcomes in LMICs is required, especially evidence from longitudinal studies investigating a wider range of outcomes. To date, there is limited evidence on the impact of the COVID-19 pandemic on IPV during pregnancy in LMICs, and this should be prioritized as the pandemic continues to affect women's access to social support globally.